UPAYA MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA MATERI TEKS EKSPLANASI MENGGUNAKAN MODEL INKUIRI BERBANTUAN MEDIA VIDEO PADA SISWA KELAS XI SMA NEGERI 3 TEBO TAHUN PELAJARAN 2019/2020 - DORLAN PARULIAN SAGALA (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2022)
The purpose of the study was to improve learning achievement in Indonesian Explanatory Text Material for students of class XI IPA-1 SMA Negeri 3 Tebo Jambi Province in semester 1 of the 2019/2020 academic year through the application of video-assisted inquiry learning models. This research is Classroom Action Research (CAR) which is carried out for 3 months at least 2 cycles. The subjects in this study were 33 students of class XI IPA-1 SMA Negeri 3 Tebo, Jambi Province. The technique of collecting student achievement data is with a learning achievement test. Technical data analysis is quantitative data analysis, namely the average value of student achievement test. The results of this study are that the application of the inquiry learning model assisted by video media can improve the learning achievement of Indonesian Explanatory Text Materials for class XI IPA-1 students of SMA Negeri 3 Tebo Jambi Province in semester 1 of the 2019/2020 academic year as evidenced by an increase in student achievement in pre-cycle the percentage of learning completeness was 42.42% then increased in the first cycle to 63.64% and increased again in the second cycle to 81.82% while the average value of the class in the pre-cycle the average value of students was at 60, 61 with 14 students who completed from 33 students. In the first cycle, the average value of the student achievement class was 71.67 with 21 students who completed from 33 students, this result had not reached the minimum criteria for completeness of 70, so it was necessary to carry out cycle II. In Cycle II, the average value of the student learning achievement class has reached the minimum criteria for completeness of 70%, namely at number 82.12 with 27 students who completed out of 33 students in learning Indonesian Explanatory Text Material. ABSTRAKTujuan penelitian adalah untuk peningkatkan prestasi belajar Bahasa Indonesia Materi Teks Eksplanasi pada siswa kelas XI IPA-1 SMA Negeri 3 Tebo Provinsi Jambi semester 1 tahun pelajaran 2019/2020 melalui penerapan model pembelajaran inkuiri berbantuan media video. Penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan selama 3 bulan minimal 2 siklus. Subjek pada penelitian ini adalah 33 Siswa kelas XI IPA-1 SMA Negeri 3 Tebo Provinsi Jambi. Teknik pengumpulan data prestasi belajar siswa dengan tes prestasi belajar. Teknis analisis data adalah analisis data kuantitatif, yaitu rata-rata nilai tes prestasi belajar siswa. Hasil dari penelitian ini adalah bahwa penerapan model pembelajaran inkuiri berbantuan media video dapat meningkatkan prestasi belajar Bahasa Indonesia Materi Teks Eksplanasi siswa kelas XI IPA-1 SMA Negeri 3 Tebo Provinsi Jambi semester 1 tahun ajaran 2019/2020 yang dibuktikan dengan adanya peningkatan prestasi belajar siswa pada pra siklus persentase ketuntasan belajar 42,42% kemudian meningkat pada siklus I menjadi 63,64% dan meningkat lagi pada siklus II menjadu 81,82% sedangkan nilai rata-rata kelas pada pra-siklus nilai rata-rata siswa berada pada angka 60,61 dengan 14 siswa yang tuntas dari 33 siswa. Pada siklus I nilai rata-rata kelas prestasi belajar siswa sebesar 71,67 dengan 21 siswa yang tuntas dari 33 siswa, hasil ini belum mencapai kriteria minimal ketuntasan ?70, sehingga perlu dilaksanakan siklus II. Pada Siklus II nilai rata-rata kelas prestasi belajar siswa sudah mencapai kriteria minimal ketuntasan ?70% yaitu pada angka 82,12 dengan 27 siswa yang tuntas dari 33 siswa dalam pembelajaran Bahasa Indonesia Materi Teks Eksplanasi.